A Barter System for Used Palm Oil Traders: Islamic Law Perspective - Muhamad Subhi Apriantoro; Yasir Hasanridhlo; Widhi Indira Laksmi; Leny Agustin; Muhammad Zakir Husain (Walidem Institute and Publishing (WIP), 2023)
This study aimed to determine the practice of purchasing and selling used cooking oil utilizing a barter system at UD Jelantah Sejahtera and examine the applicable Islamic law. This study employs a qualitative methodology with a deductive approach. There are two types of data sources: primary and secondary. The statistics were gathered through direct interviews with UD Jelantah Sejahtera Karanganyar, an oil collector, and three clients. Secondary data was gathered from many books, journals, and websites. The findings of this study are the barter mechanism or service of exchanging used goods for consumable goods, namely the exchange of used cooking oil products for good oil that is suitable for use in cooking. However, the oil exchanged by UD Jelantah Sejahtera is vegetable oil, such as cooking oil, that is no longer suitable for use and is commonly referred to as waste oil. Trading old cooking oil for fresh packaged cooking oil of varied quantities or volumes is allowed because cooking oil is not an Indonesian staple.